Stimulation of Non-canonical NF-κB Through Lymphotoxin-β-Receptor Impairs Myogenic Differentiation and Regeneration of Skeletal Muscle - Schmidt, Manuel; Weidemann, Anja; Poser, Christine; Bigot, Anne; von Maltzahn, Julia (Frontiers in Cell and Developmental Biology, 2021)
Myogenic differentiation, muscle stem cell functionality and regeneration of skeletal muscle are cellular processes partially under tight control of various signaling pathways. Here, we investigated the role of non-canonical NF-κB signaling in myogenic differentiation, muscle stem cell functionality and regeneration of skeletal muscle. We stimulated non-canonical NF-κB signaling through an agonist of the lymphotoxin beta receptor (LTβR). Interestingly, we found that stimulation of non-canonical NF-κB signaling through the LTβR agonist impairs myogenic differentiation, muscle stem cell function and regeneration of skeletal muscle. Furthermore, we could show that stimulation of non-canonical NF-κB signaling by the LTβR agonist coincides with activation of canonical NF-κB signaling. We suggest a direct crosstalk between canonical and non-canonical NF-κB signaling during myogenic differentiation which is required for proper myogenic differentiation and thereby regeneration of skeletal muscle.